Signalling networks in cholangiocarcinoma: Molecular pathogenesis, targeted therapies and drug resistance. (20th May 2019) - Fouassier, Laura; Marzioni, Marco; Afonso, Marta B.; Dooley, Steven; Gaston, Kevin; Giannelli, Gianluigi; Rodrigues, Cecilia M. P.; Lozano, Elisa; Mancarella, Serena; Segatto, Oreste; Vaquero, Javier; Marin, Jose J. G.; et al.
Abstract: Cholangiocarcinoma (CCA) is a deadly disease. While surgery may attain cure in a minor fraction of cases, therapeutic options in either the adjuvant or advanced setting are limited. The possibility of advancing the efficacy of therapeutic approaches to CCA relies on understanding its molecular pathogenesis and developing rational therapies aimed at interfering with oncogenic signalling networks that drive and sustain cholangiocarcinogenesis. These efforts are complicated by the intricate biology of CCA, which integrates not only the driving force of tumour cell‐intrinsic alterations at the genetic and epigenetic level but also pro‐tumorigenic cues conveyed to CCA cells by different cell types present in the rich tumour stroma. Herein, we review our current understanding of the mechanistic bases underpinning the activation of major oncogenic pathways causative of CCA pathogenesis. We subsequently discuss how this knowledge is being exploited to implement rationale‐based and genotype‐matched therapeutic approaches that predictably will radically transform CCA clinical management in the next decade. We conclude by highlighting the mechanisms of therapeutic resistance in CCA and reviewing innovative approaches to combat resistance at the preclinical and clinical level.